Uncovering aspects that facilitate a continuous improvement culture within nonprofit organizations - Almaiman, Sulaiman; McLaughlin, Patrick (Cranfield University, 2017)
The literature shows that organizational culture has a significant impact on implementing and sustaining continuous improvement initiatives, although there is a lack of research on how to achieve this impact. Therefore, this action research adopts a grounded theory approach to explore aspects of organizational culture that facilitate continuous improvement. Eighteen interviews in nine nonprofit organizations yielded data which, when analysed revealed forty emergent factors, classifiable into six core themes developed by the participants during two focus group discussions. These themes conceptualized by Schain's model of organizational culture.
Keywords: Organizational culture; Continuous improvement; Nonprofit organizations